The Effect of Viral Marketing, Celebrity Endorser, and Brand Awareness on Purchase Decisions for Skintific Products at STIE Malangkucecwara with Trust as an Intervening Variable - Imama Zuhroh; Yuyuk Liana; Christina Natalia Tedjautama (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of viral marketing, celebrity endorser, and brand awareness on the purchase decision for Skintific products at STIE Malangkucecwara, with consumer trust as an intervening variable. The study employs a quantitative approach using a survey method with accidental sampling, involving 89 female student respondents. Data were collected via questionnaire and analyzed using multiple linear regression and the Sobel test. Results indicate that viral marketing, celebrity endorser, and brand awareness each have a positive and significant effect on purchase decisions. Consumer trust also proved to mediate the relationships between all three independent variables and purchase decisions. These findings provide practical implications for skincare marketing strategies, particularly in building consumer trust through digital content and collaboration with credible influencers.